Facilitating internal motivation: Impacts of the Life Code Matrix model on working life - Owler, K (My University, 2012)
One of the key challenges of coaching is facilitating internal motivation in clients. The Life Code Matrix model (LCM) was designed to overcome this challenge. The research discussed in this paper aimed to evaluate the LCM process and its impact on the lives of working adults. Data suggested that LCM was effective in supporting internal motivation for the majority of research participants. The method can also improve worker confidence and capacity to learn and help develop positive work-place relationships. Finally, it may be useful to support work-place engagement.
Keywords: Work; Internal motivation; transition; strengths; wellbeing; identity; engagement